Interleukin-6 In Rheumatoid Arthritis - From The Laboratory To The Bedside - Liu, Xiao; J. Teichtahl, Andrew; P. Wicks, Ian (Current Pharmaceutical Design, 2015)
Rheumatoid arthritis (RA) is a common and debilitating disease. Expanded therapeutic options, targeting pro-inflammatory cytokines such as tumour necrosis factor (TNF) and interleukin-6 (IL-6), have revolutionised RA treatment. To date, efficacy data shows superiority of IL-6 inhibition over placebo, conventional disease modifying anti-rheumatic drugs such as methotrexate, and TNF inhibition. Moreover, while demonstrating some key differences in the safety profile compared with TNF inhibition (e.g. hyperlipidemia and neutropenia), these safety concerns have not, at least to date, been found to cause clinically significant adverse outcomes. Other safety parameters, such as infection and malignancy rates have been found to be comparable between IL-6 and TNF inhibition. This review explores the biology and clinical applications of IL-6 inhibition in the management of RA.
Keywords: interleukin-6